2022
DOI: 10.3389/fcell.2022.777844
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Transporter Gene Expression in the Early Conceptus—Implications From Two Mouse Models of Diabetic Pregnancy

Abstract: Maternal diabetes in early pregnancy increases the risk for birth defects in the offspring, particularly heart, and neural tube defects. While elevated glucose levels are characteristic for diabetic pregnancies, these are also accompanied by hyperlipidemia, indicating altered nutrient availability. We therefore investigated whether changes in the expression of nutrient transporters at the conception site or in the early post-implantation embryo could account for increased birth defect incidence at later develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 93 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Yet, their expression did not significantly differ between metabolic conditions. When interrogated for all genes with Slc (solute carrier) nomenclature, this dataset also did not reveal significant differences for over 200 nutrient transporter genes expressed at this stage (Kappen et al, 2022). Taking together our quantitative and qualitative data, they do not provide evidence that altered gene expression in lipid-related pathways could be invoked as causes for the excess lipid accumulation in any of our three experimental models.…”
Section: Expression Of Lipid Transporter Proteins In Yolk Sacs From P...mentioning
confidence: 70%
See 2 more Smart Citations
“…Yet, their expression did not significantly differ between metabolic conditions. When interrogated for all genes with Slc (solute carrier) nomenclature, this dataset also did not reveal significant differences for over 200 nutrient transporter genes expressed at this stage (Kappen et al, 2022). Taking together our quantitative and qualitative data, they do not provide evidence that altered gene expression in lipid-related pathways could be invoked as causes for the excess lipid accumulation in any of our three experimental models.…”
Section: Expression Of Lipid Transporter Proteins In Yolk Sacs From P...mentioning
confidence: 70%
“…Thus, lipids are either taken up from the maternal circulation, where they are in excess supply due to maternal hyperlipidemia in diabetic pregnancies, or they would have to be synthesized in visceral yolk sac from the excess msternal glucose under hyperglycemic conditions. We have previously shown that in addition to Glut3, the visceral yolk sac expresses the highcapacity glucose transporter Glut2, specifically in the endodermal cell layer (Kappen et al, 2022), lending plausibility to excessive glucose uptake. We here show that lipid transporters ApoA1, ApoB, SR-B1 and Cubilin are also expressed in the visceral yolk sac, with Cubilin and SR-B1 restricted to the endodermal layer, while ApoA1 and ApoB are also found in the mesodermal compartment of the visceral yolk sac, consistent with prior literature (Shi and Heath, 1984;Farese et al, 1996;Terasawa et al, 1999;Strope et al, 2004;Santander et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA extraction, library preparation, and RNA sequencing RNA was extracted using the Trizol protocol (Kappen et al, 2022), and quality was assessed on an Agilent Bioanalyzer 2,100 (Agilent Technologies, Santa Clara, CA); only samples with an RNA Integrity Index larger than 7 were used in subsequent experiments. 50 ng of total RNA per sample were used to construct Illuminacompatible RNA sequencing libraries, applying the Lexogen 3′-Quant-Seq method, and utilizing Unique Molecular Identifiers (UMI) in order to guard against PCR-based artefacts when counting sequencing reads (reagents and protocol from Lexogen, Inc., Greenland, NH).…”
Section: Animalsmentioning
confidence: 99%